IMPLEMENTASI PERATURAN DAERAH KOTA PEKANBARU NOMOR 8 TAHUN 2014 TENTANG PENGELOLAAN SAMPAH - Rezeki, Jayanthi Sri; Rusli, Zaili; R.F.S, Harapan Tua (Jurnal Ilmu Administrasi Negara, 2018)
Implementation of Regional Regulation of Pekanbaru City Number 8 Year 2014 on Waste Management. This study aims to determine the implementation of Perda Pekanbaru No. 8 of 2014 on waste management. This study used descriptive qualitative method. Primary data obtained directly through interviews from key informan, namely Head of LKMD, Head of RW. Secondary data were obtained from research documents. The results showed that the elements of communication factors support the successful implementation of Regional Regulation No. 8 of 2014 in Simpang Tiga Village. Elements of the resource factor support the successful implementation of Local Regulation No. 8 of 2014 in Simpang Tiga Village, but support from the equitable distribution of human resources quality, availability of facilities and incentives is still inadequate. Similarly, elements of the disposition factor and elements of the bureaucratic structural factor also support the successful implementation of Regional Regulation No. 8 of 2014 in Simpang Tiga Village. The inhibiting factors include uneven quality of human resources, inadequate facilities, poor compliance. The supporting factors in the implementation of Regional Regulation No. 8 of 2014 include: leadership, organizational structure, number of administrators, offices, infrastructure and facilities, clear legal basis, increasing number of migrants, and rapid urban development.